2017
DOI: 10.5696/2156-9614-7.15.1
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Environmental and Public Health Problem of Electronic Waste in India

Abstract: Background.Monumental progress has been made in the area of information and communication technology, leading to a tremendous increase in use of electronic equipment, especially computers and mobile phones. The expansion of production and consumption of electronic equipment along with its shorter life span has led to the generation of tremendous amounts of electronic waste (e-waste). In addition, there is a high level of trans-boundary movement of these devices as second-hand electronic equipment from develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Such activities usually involve child labour [89][90][91][92][93]. In India, approximately 35,000 to 500,000 child workers less than 16 years of age are active in different phases of e-waste activities [94,95]. Cordova-Pizarro et al [61] also confirmed the existence of the activity of child labour among Mexican e-waste workers whose ages ranged between 8 and 15 years.…”
Section: Informal Activitiesmentioning
confidence: 99%
“…Such activities usually involve child labour [89][90][91][92][93]. In India, approximately 35,000 to 500,000 child workers less than 16 years of age are active in different phases of e-waste activities [94,95]. Cordova-Pizarro et al [61] also confirmed the existence of the activity of child labour among Mexican e-waste workers whose ages ranged between 8 and 15 years.…”
Section: Informal Activitiesmentioning
confidence: 99%
“…India being one of the most emerging and largest developing countries with the second largest populated country in the world has reported to generate 2.1 Mt of E-waste in 2019 [ 132 ]. A study conducted by ASSOCHAM-KPMG, 2018 has reported that India is one of the world’s second-largest mobile markets [ 133 ] and likewise the fourth largest producer of E-waste [ 8 ].Additionally, the illegal trading and importing of scarp waste from other countries is one of the mammoth tasks to handle the waste management at a large [ 134 , 135 ]. Also, due to the unavailability of appropriate treatment methods, India is currently facing a huge threat toward the entire value chain management of the waste along with the booming challenge of 95% backyard recycling [ 136 – 139 ].…”
Section: E-waste Management In India -At a Glancementioning
confidence: 99%
“…As the winter arrives, a slight dip in the temperature aggravates the situation with 'temperature inversion' leaving pollutants hanging low in the atmosphere as the vertical wind movement gets lowered. 17 This makes air pollution an acute problem in the city during winters when the Air Quality index rises above 300/400. There is smog everywhere and situation is worst at the time of Diwali when firecrackers are burnt, people sit around fire burning wood to keep themselves warm.…”
Section: What Are the Causes Of Such Rapid Increase In Air Pollution?mentioning
confidence: 99%